ANALISA PENGETAHUAN IBU TENTANG TUMBUH KEMBANG BALITA DENGAN PARTISIPASI PENIMBANGAN BALITA DI POSYANDU ANGGREK KELURAHAN POPONGAN KABUPATEN SEMARANG - Widyah Setiyowati; Titik Kurniawati; Akhid Suraiya (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
Increased community participation at the village level and community families, especially in the development of maternal, child and family health which are priorities for health development through the Village Community Health Development approach, which is manifested in the form of developing and fostering posyandu, and so on. Posyandu is one of the supporting faktors indispensable for monitoring the growth of their children. The purpose of this study was to analyze the relationship between maternal knowledge about toddler growth and development with participation in weighing children under five at Posyandu Anggrek, Popongan Village, Semarang Regency. This type of research is a correlative study with a cross sectional approach. The population in this study were all mothers who had toddlers at the Posyandu Anggrek, Popongan Village, Semarang Regency, as many as 59 samples of women who obtained 37 respondents. The results showed that most of the knowledge of mothers under five is in the good category, namely 34 respondents (91.9%). Most of the participation of mothers to come to the posyandu is in the participation category, namely 27 respondents (73.0%). There is a significant relationship between the level of maternal knowledge about toddler growth and development with participation in weighing children under five at the Posyandu Anggrek, Popongan Village, Semarang Regency with a p value of 0.798 (p 0.05). Suggestions to the community, especially mothers and families with toddlers to always be active in visiting to the posyandu so that growth and development can be monitored.